Visionary Leadership and Its Influence on School Culture - M. Munif (Agrapana Media, 2025)
A weak school culture often becomes an obstacle in achieving sustainable educational quality. The problems that arise include low teacher participation, weak collaboration among school members, and the lack of visionary leadership capable of inspiring all elements within the educational institution. This study aims to analyze the role of visionary leadership in strengthening school culture, particularly how a leader’s vision, values, and exemplary behavior influence the formation of an educational organization’s character. The method used is a Systematic Literature Review (SLR) by examining various previous studies relevant to visionary leadership and school culture across different educational contexts. The findings indicate that visionary leadership has a significant influence on improving teachers’ work ethic, collaboration, and innovation, as well as contributing to the creation of a positive and adaptive school culture. The implication of this study emphasizes the importance of strengthening visionary leadership capacity among school principals to build an organizational culture that is characterized, participatory, and oriented toward sustainable educational quality.